2021
DOI: 10.3389/fphar.2021.664697
|View full text |Cite
|
Sign up to set email alerts
|

Sesamolin Protects Mice From Ovariectomized Bone Loss by Inhibiting Osteoclastogenesis and RANKL-Mediated NF-κB and MAPK Signaling Pathways

Abstract: This article was submitted to Experimental Pharmacology and Drug Discovery, a section of the journal Frontiers in Pharmacology. Postmenopausal osteoporosis (PMOP), which increases the risk of fracture, is the most common bone disease in women. PMOP not only increases the risk of death but also imposes a financial burden on countless families. At present, most of the drugs used to treat osteoporosis have significant side effects, so it is important to find effective anti-osteoporosis medications without major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…The MAPK signalling pathway includes ERK, JNK, and p38 pathways (Yang et al. 2021 ). In addition, the phosphorylation of MAPKs (ERK, JNK and p38) is conducive to RANKL-stimulated osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signalling pathway includes ERK, JNK, and p38 pathways (Yang et al. 2021 ). In addition, the phosphorylation of MAPKs (ERK, JNK and p38) is conducive to RANKL-stimulated osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the MAPK signaling pathway is highly involved in osteoclast differentiation and actively regulates osteoclast maturity ( Fang et al, 2021 ; Yang et al, 2021 ). To explore the response mechanism by which Uro-A inhibits osteoclasts, we tested the expression of the MAPK family after Uro-A treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Only sesamol gave the 50% inhibitory concentration (IC 50 ) against melanoma despite required a high treatment concentration (1893.1 ± 170.7 µM). It was mentioned in the study that sesamolin could not be dissolved well in cell culture media at a concentration higher than 200 µM that causing the limit investigation at a higher concentration [ 65 ]. These findings suggest that although sesamolin had the potency to inhibit melanoma cell growth, the limitation related to the solubility hindered the cytotoxic effect.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Several studies have used animal models to study the pharmacological activity of sesamolin and other lignans in sesame seeds or oils. However, they did not report the pharmacokinetic profile of sesamolin after administration [43,[63][64][65]. Two studies reported the bioavailability of sesamolin in in vivo models.…”
Section: Pharmacokineticsmentioning
confidence: 99%